University Differences in the Graduation of Minorities in STEM Fields: Evidence from California - Arcidiacono, Peter; Aucejo, Esteban M.; Hotz, V. Joseph (American Economic Review, 2016)
We examine differences in minority science graduation rates among University of California campuses when racial preferences were in place. Less prepared minorities at higher ranked campuses had lower persistence rates in science and took longer to graduate. We estimate a model of students' college major choice where net returns of a science major differ across campuses and student preparation. We find less prepared minority students at top ranked campuses would have higher science graduation rates had they attended lower ranked campuses. Better matching of science students to universities by preparation and providing information about students' prospects in different major-university combinations could increase minority science graduation.